The influence of Margaret Sanger and Theinternational Planned Parenthood Federation inpromoting the control of birth in the United States and Chile - Iñiguez Manso, Andrea (Derecho Público Iberoamericano, 2018)
This article has the purpose to illustrate the reader about the influence that Margaret Sanger and the International Planned Parenthood Federation have had in the promotion of birth control, and analyze if those activities have the purpose, as is it has been said, of improving the life quality of the people and the protection of the right to private life or, on the contrary, is an undercover strategy of promoting the agendas of eugenics and population control.